2013
DOI: 10.1002/bmb.20754
|View full text |Cite
|
Sign up to set email alerts
|

Using an ePortfolio system as an electronic laboratory notebook in undergraduate biochemistry and molecular biology practical classes

Abstract: Despite many apparent advantages, including security, back-up, remote access, workflow, and data management,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…1,2 Out of the many options for ELNs, OneNote stands out as a solid option to use for undergraduate lab reports. [3][4][5][6][7][8] With minimal amount of faculty setup OneNote has been an excellent ELN for my biochemistry I and II labs and has been well received by my students.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Out of the many options for ELNs, OneNote stands out as a solid option to use for undergraduate lab reports. [3][4][5][6][7][8] With minimal amount of faculty setup OneNote has been an excellent ELN for my biochemistry I and II labs and has been well received by my students.…”
Section: Introductionmentioning
confidence: 99%
“…Although expert structure elucidation software packages (computer‐aided structure elucidation) do exist from commercial and free software providers, they are still not commonly used in academia. Rather, they remain yet isolated solutions in an environment where electronic laboratory notebooks are very uncommon and most other analytical data are handled in hardcopy. NMR processing and analysis software packages have become very powerful tools but are often only used as a vehicle to produce printout spectra like in the predigital era.…”
Section: What Is Small Molecules Structure Elucidation In “Routine Nmmentioning
confidence: 99%
“…The authors concluded that the introduction of the ELN in class produced some benefits for students-they were more prepared for classes, more creative, and engaged in class. Some negative outcomes, such as increased workload for the instructor and disruption of class dynamics, were also reported (Johnston et al, 2014).…”
Section: Introducing Elns In Academic Institutionsmentioning
confidence: 99%